Techno-Economic Analysis of Betaine Surfactant Production from Hydrogenated Palm Kernel Oil: A Preliminary Plant Design - Oktariandi. M, Vito; Agustia Putri, Wahyuni; Saridiyah, Saridiyah; Legawati, Lisa; Zulfansyah, Zulfansyah (SURYA TEKNIKA, 2026)
Indonesia's high dependency on betaine surfactant imports, which grow at 8.15% per year, necessitates the development of domestic production based on local raw materials. This study aims to design an Amidopropyl Betaine plant from Hydrogenated Palm Kernel Oil (HPKO) with a capacity of 20,000 tons per year. The production process consists of three main stages: amidation reaction (85% conversion), separation and purification via distillation, and carboxymethylation reaction (99% conversion). An economic feasibility analysis yielded a Net Present Value (NPV) of Rp 325 billion, Return on Investment (ROI) of 36.93%, Payback Period (PBP) of 1.53 years, Internal Rate of Return (IRR) of  29,38%, and Break-Even Point (BEP) of 35.84%, indicating that the plant is highly feasible and profitable. This study concludes that the establishment of an HPKO-based betaine surfactant plant is not only techno- economically feasible but also strategic for reducing import dependency and adding value to the national palm oil industry.